THE RELATION AMONG ETHNICS IN HIGHER EDUCATIONAL INSTITUTION FROM THE PERSPECTIVE OF ETHNOGRAPHY - Dawi, Amir Hassan; Dawi, Faridah Karim; Mustapha, Ramlee; Ahmad, Abdul Razak (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2009)
The relation of ethnics refers to interaction among different ethnics (interethnic) or interaction in the same ethnical groups (intraethnic). The correlation of ethnic in this chapter focuses on the correlation among ethnics (interethnic). The relation among ethnics or peoples has been the main issue discussed in many countries whose citizens are from multi-ethnic. Groups of ethnics building â€œsocial borderâ€ among the ethnics are potential to create conflicts among them. Social border among ethnics can also cause dissatisfaction which is represented by particular social actions that can lead the people to open and bleed conflicts. An example of real ethnical conflict occurred in the ex-United of Yugoslavia, where a business of an ethic causing destruction to other ethnic and consequently led to the ruin of the country.